2021
DOI: 10.3389/fpubh.2021.622677
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Help-Seeking and Associated Factors Among Public Health Workers During the COVID-19 Outbreak in China

Abstract: Background: The COVID-19 outbreak in China has created multiple stressors that threaten individuals' mental health, especially among public health workers (PHW) who are devoted to COVID-19 control and prevention work. This study aimed to investigate the prevalence of mental help-seeking and associated factors among PHW using Andersen's Behavioral Model of Health Services Use (BMHSU).Methods: A cross-sectional survey was conducted among 9,475 PHW in five provinces across China between February 18 and March 1, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 45 publications
5
28
4
Order By: Relevance
“…However, during the pandemic in China, when small-scale outbreaks occurred in some areas, primary PHWs were on the front line of the fight against the epidemic and were required to respond quickly to their areas of responsibility 42. Consequently, they were exposed to greater workload, physical injuries and mental stress caused by higher work demands, with insufficient work resources, which seriously deteriorated their job satisfaction 43. The results showed that the thriving at work score of primary PHWs was 3.17±0.65.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the pandemic in China, when small-scale outbreaks occurred in some areas, primary PHWs were on the front line of the fight against the epidemic and were required to respond quickly to their areas of responsibility 42. Consequently, they were exposed to greater workload, physical injuries and mental stress caused by higher work demands, with insufficient work resources, which seriously deteriorated their job satisfaction 43. The results showed that the thriving at work score of primary PHWs was 3.17±0.65.…”
Section: Discussionmentioning
confidence: 99%
“…Supports from colleagues, supervisors and families were the fundamental, which could encourage HCWs to fight with confidence, help HCWs control negative thoughts and relieve their psychological burden and miss (Blanco‐Donoso et al, 2020 ). Support from society gave a great and warm respect to HCWs' contribution and encouraged HCWs to seek mental help, which might increase HCWs' self‐efficacy and turn the trauma into positive growth (She et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that the COVID-19 cases would affect the investment and trust behavior, and the physical activity of the public (20)(21)(22). The OPHS behavior affected by the COVID-19 cases was also investigated among the public workers and college students (23,24). However, how the OPHS behavior of the Chinese public was affected by the COVID-19 cases has not yet been understood.…”
Section: Introductionmentioning
confidence: 99%